2020
DOI: 10.3390/membranes10100256
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an Integrated Membrane Process with Electrochemical Pre-Treatment on Poultry Slaughterhouse Wastewater Purification

Abstract: Industrial activities produce a variety of pollutants that may not be easily treated using centralized wastewater treatment systems based on a single treatment unit. The variability of the pollutants brings the importance of industrial-specific integrated wastewater treatment plants such as integrated membrane filtration systems. However, the performance of a membrane filtration process can be highly affected by the presence of high amounts of suspended particles in the raw wastewater. Therefore, proper select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Recently, a study conducted by Meiramkulova et al (2021) identified some pathogenic microbes (Salmonella coliphages, Pseudomonas aeruginosa, and Staphylococcus aureus, Enterococcus etc.) in wastewater samples collected from the Izhevsk PC poultry slaughterhouse located in Izhevsk village, Arshalinsky District, in the Akmola Region of the Republic of Kazakhstan [17]. Other characterization studies assessed potential for strains to be used as biomarkers for tracking indicators of contamination.…”
Section: Biological Activitymentioning
confidence: 99%
“…Recently, a study conducted by Meiramkulova et al (2021) identified some pathogenic microbes (Salmonella coliphages, Pseudomonas aeruginosa, and Staphylococcus aureus, Enterococcus etc.) in wastewater samples collected from the Izhevsk PC poultry slaughterhouse located in Izhevsk village, Arshalinsky District, in the Akmola Region of the Republic of Kazakhstan [17]. Other characterization studies assessed potential for strains to be used as biomarkers for tracking indicators of contamination.…”
Section: Biological Activitymentioning
confidence: 99%
“…Without proper pretreatment, membranes will suffer severe membrane fouling, hindering the membrane performance, and some heavy fouling could even cause membrane failure. For example, Meiramkulova et al [21] investigated the performance of an integrated membrane process with electrochemical pretreatment on PSWW purification, and their findings showed that the electrochemical pretreatment was highly efficient at reducing turbidity, color, TSS, COD, and BOD by 71-85%. In addition, the pretreatment resulted in a low rate of cake formation on the membrane [21].…”
Section: Conventional Treatment Of Poultry Slaughterhouse Wastewater As Pretreatment Prior To Membrane Separationmentioning
confidence: 99%
“…In a study by Sardari et al (2018), EC was followed by ultrafiltration for treating PSW and 5 minutes of electrolysis time reduced fouling on the ultrafiltration membrane significantly. Meiramkulova et al (2020a) investigated the performance of an integrated membrane process with EC pre-treatment on PSW. The findings showed that EC pre-treatment unit was highly effective for the removal of parameters such as turbidity, colour, TSS, COD, and BOD by 71-85%.…”
Section: Electrocoagulation Followed By Membrane Treatment Systemmentioning
confidence: 99%